Effect of grafting on resistance to vine decline disease, yield and fruit quality in muskmelon cv. Sawadi - Qais Al-Mawaali (Journal of Agricultural and Marine Sciences, 2019)
A study was conducted to evaluate graft success, resistance to vine decline disease and effect of grafting on quality and yield of muskmelon. Two field experiments, conducted in Oman, showed that muskmelon cv. Sawadi grafted on six cucurbit rootstocks gave high grafting success: 97.6-99.1% (avg. 98.6%) and 92.4-96.9% (avg. 95.3%) under field conditions in fall 2012 and spring 2013 respectively. No significant differences were observed between seasons among the six treatments and a non-grafted control in consumer preference for odor and firmness, fruit shape, flesh vitamin C, micronutrient content  and TSS (sucrose %) or pH in spring 2013 (P > 0.05). The concentration of phosphorus and sodium significantly decreased in both seasons in all treatments in comparison to the control (P > 0.05). In both seasons potassium content significantly increased when Rsscih7458 and Mubyeongjangsoo rootstocks were used (P < 0.05). Strong Tosa rootstocks showed zero graft failure, high resistance to vine decline disease, high yield production and higher TSS (sucrose %) as compared to other rootstocks. Strong Tosa and Tetsukabuto rootstocks showed significantly higher consumer acceptance for rind color, flesh color and overall consumer acceptance in spring 2013 and was also less affected by seasonal changes. Results suggested that by grafting muskmelon cv. Sawadi some quality attributes may be improved in addition to the increased level of resistance to disease. However, additional trials are required to make final recommendations for the farming community.